Jaki synaksarion Sawa Nemanjić nadał Chilandarowi? Aktualny stan wiedzy - Szefliński, Błażej (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2025)
The article presents the current state of knowledge on the synaxarion introduced by Sava Nemanjić in the Chilandar monastery founded by him and his father. It discusses all the hypotheses formulated so far and related observations presented in the latest publications. The current state of knowledge seems to suggest that Miladin Mitrović’s hypothesis is the most likely, according to which the Evergetian liturgical practice was introduced in Chilandar, but without translating the synaxarion into Church Slavonic. Instead, the rubrics from the synaxarion were added to other liturgical books – menaia, triodia, and octoechoi.